Alvenaria estrutural com blocos de concreto: propriedades mecânicas residuais de argamassas, grautes e prismas submetidos a altas temperaturas - Leal, Cleber Eduardo Fernandes (Universidade Federal de São Carlos, 2023)
The study of structural masonry under high temperatures is still initial in Brazil. Even internationally, little is known about the thermal and mechanical properties of masonry components when overheated. In the absence of a specific Brazilian standard, foreign guidelines are adopted by the technical community to check structural masonry in fire situations. However, its applicability is questionable, given that Brazilian materials have different characteristics of geometry and composition, in addition to the associated construction practices. Despite these differences, most international design/verification procedures are based on full-scale wall tests which, due to the lack of conveniently equipped laboratories, are not yet viable in our country. Therefore, a more feasible approach would be the correlation between test results, under high temperatures, of smaller models (blocks, prisms, small walls) and larger models (full-size walls), like what is done at room temperature. For that matter, this research aimed to determine the residual mechanical behavior of laying mortars, grouts, and prisms with two concrete blocks. There is no national, or even international, procedure for assessments of this nature in structural masonry prisms. The method used corresponded to an adaptation of that proposed by Medeiros, Parsekian and Moreno Jr. (2022) for the use of RILEM TC 200-HTC:2007 curves in structural concrete blocks. Were produced mortars with lime (conventional), lime-free (industrialized) and from three resistance classes (5, 10 and 20 MPa); grouts with 15, 25 and 35 MPa; prisms with two hollow and uncoated concrete blocks, varying block strength (6, 12, and 24 MPa), composition and strength of the laying mortar. All materials were subjected to low heating rates (4°C/min for mortars and 1°C/min for others) until they reached 200, 400, 600 and 800°C; kept for one hour at the respective temperatures; and cooled at the same rates to temperatures close to ambient. After cooling, the residual values of compressive strength and secant deformation modulus were obtained via destructive tests. The results showed that lime significantly interfered with the degradation of the mortars, especially after 400°C. The rehydration of the binder led to expansion, cracking, and greater reductions in the ordinary mixtures. Even with small amounts of lime, the grouts exhibited behavior consistent with residual normative curves for ordinary concretes (ACI/TMS 216-1:2014, EN 1992-1-2: Eurocode2: 2004) and those extracted from the literature. The confinement of the mortar joint led to a delay in the degradation of the prisms' mechanical properties. The cracking observed in the mortar specimens did not occur in the prism joints, regardless of the type of mortar and exposure temperature. The prism results were consistent with those of the blocks tested by Medeiros (2022). For all the materials tested, the drying modulus decreased early compared to the compressive strength. After 800°C, the property value became negligible. As a contribution, normalized mechanical property degradation curves were proposed for each material investigated.
Structural masonry with concrete units: residual mechanical properties of mortars, grouts and prisms submitted to high temperatures
Keywords: Alvenaria estrutural; Structural masonry; Altas temperaturas; High temperatures; Propriedades mecânicas; Mechanical properties; Resistência residual; Residual strength; Análise experimental; Testing; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS